2013
DOI: 10.1115/1.4023690
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Zigzag Functions in Equivalent Single Layer Theories for Laminated Composite and Sandwich Beams: A Comparative Study and Some Observations on External Weak Layers

Abstract: The paper presents a comparison between two existing zigzag functions that are used to improve equivalent single layer (ESL) theories for the analysis of multilayered composite and sandwich beams. ESL theories are easy to implement and computationally affordable but, in order to correctly describe the mechanical behavior of laminated structures (especially those exhibiting high transverse anisotropy or high thickness-to-side length ratios), the displacement field needs to be enriched by a through-the-thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 95 publications
(201 reference statements)
3
64
0
Order By: Relevance
“…Recently, Gherlone [35] and the present authors [31] have shown that MZZF suffers from certain limitations for sandwiches with large face-to-core stiffness ratios and arbitrary layups, as the MZZF is not based on actual transverse shear moduli that drive the underlying physics of the problem. As an alternative ZZ function, the Refined Zigzag Theory (RZT) developed by Tessler, Di Sciuva and Gherlone [36][37][38][39] may be used.…”
Section: Mixed-variational Theoriesmentioning
confidence: 84%
“…Recently, Gherlone [35] and the present authors [31] have shown that MZZF suffers from certain limitations for sandwiches with large face-to-core stiffness ratios and arbitrary layups, as the MZZF is not based on actual transverse shear moduli that drive the underlying physics of the problem. As an alternative ZZ function, the Refined Zigzag Theory (RZT) developed by Tessler, Di Sciuva and Gherlone [36][37][38][39] may be used.…”
Section: Mixed-variational Theoriesmentioning
confidence: 84%
“…It is reminded that in [55] this model has been already proven to be accurate and computationally efficient when closed form solutions are considered, since it achieves the accuracy of layerwise models with just five d.o.f. Therefore, the aim of present numerical results is neither that of: a) discussing the advantages of the zigzag modeling approach here used, nor discussing the advantages offered by its variable kinematics, as both aspects have been already comprehensively overviewed in [43,[51][52][53][54][55][56]; b) nor discussing the relative merits of a physically-based zigzag representation like the present one over the Murakami's zigzag function just based upon kinematic assumptions, because both modeling options have been already compared and extensively discussed in [17]; c) finally, nor comparing the available displacement-based and mixed theories incorporating zigzag functions to other existing models and nor to discuss their fidelity to 3D exact elasticity or finite element solutions, since assessments were already given among many others in the references quoted in [17] that have shown their value.…”
Section: Numerical Applications and Discussionmentioning
confidence: 99%
“…As discussed by Gherlone [17], the Murakami's zigzag function that is just based upon kinematic assumptions is much easy to implement and requires a less effort than the physically consistent zigzag functions obtained through enforcement of physical conditions at the interfaces, but it is not always equally accurate. On the contrary, in the physically-based zigzag functions the slope is not forced to reverse at each interface, because as shown by exact solutions for undamaged and damaged sandwiches this neither occurs for the through-the-thickness distribution of the transverse displacement and it does not always necessarily occur for the in-plane displacement components.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations